2020
DOI: 10.1002/biot.201900329
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Biosensor Controlled by DNAzyme for On‐Site Genetic Detection of Pathogens

Abstract: On-site predetection of pathogens could significantly decrease of a disease outbreak or national loss in most of the countries. However, conventional detection techniques are limited in use for on-site detection due to the necessity of specialized skill or equipment. Therefore, it is necessary to develop a new technique that can predetect pathogens in the field without special skills or equipment. Here, a DNAzyme strategy to control a plasmonic biosensor for rapid and simple visual detection of Salmonella chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Choleraesuis, S . Typhimurium, and Salmonella specific with very high sensitivity, exhibiting a detection range from 6.76 to 50 nM with LOD 1 CFU mL −1 [ 15 ]. The species was tested using mismatched targets, called by the author M1, M2, and M3, and were designed with one, two, and three adjacent incompatibilities, presenting to be 100% specific to the bacterium of interest when tested at levels of 0–100 nM.…”
Section: First Visual Approaches To the Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…Choleraesuis, S . Typhimurium, and Salmonella specific with very high sensitivity, exhibiting a detection range from 6.76 to 50 nM with LOD 1 CFU mL −1 [ 15 ]. The species was tested using mismatched targets, called by the author M1, M2, and M3, and were designed with one, two, and three adjacent incompatibilities, presenting to be 100% specific to the bacterium of interest when tested at levels of 0–100 nM.…”
Section: First Visual Approaches To the Datasetmentioning
confidence: 99%
“…Gold is the most used material for this function because of its biocompatibility and its SPR band appearing in the visible region, which often allows detection with the naked eye ( [52,58]). AuNPs were used to improve the specificity of the probe to immobilize two different fragments in the nanoparticle for colorimetric detection of S. Choleraesuis, S. Typhimurium, and Salmonella specific with very high sensitivity, exhibiting a detection range from 6.76 to 50 nM with LOD 1 CFU mL −1 [15]. The species was tested using mismatched targets, called by the author M1, M2, and M3, and were designed with one, two, and three adjacent incompatibilities, presenting to be 100% specific to the bacterium of interest when tested at levels of 0-100 nM.…”
Section: Dna-based Nanosensor For Salmonella Spp Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al, also reported the use of DNAzyme conjugated with gold NPs for detecting Salmonella choleraesuis [ 99 ]. This study used multi-component DNAzymes for performing various functions in plasmonic biosensors.…”
Section: Dna Origami-based Plasmonic Biosensormentioning
confidence: 99%